2017
DOI: 10.1002/acm2.12086
|View full text |Cite
|
Sign up to set email alerts
|

A complete 4DCT‐ventilation functional avoidance virtual trial: Developing strategies for prospective clinical trials

Abstract: Introduction4DCT-ventilation is an exciting new imaging modality that uses 4DCT data to calculate lung-function maps. Because 4DCTs are acquired as standard of care for lung cancer patients undergoing radiotherapy, 4DCT-ventiltation provides functional information at no extra dosimetric or monetary cost to the patient. The development of clinical trials is underway to use 4DCT-ventilation imaging to spare functional lung in patients undergoing radiotherapy. The purpose of this work was to perform a virtual tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…This retrospective work on 4D CT ventilation imaging has provided the framework for design of clinical trials using 4D CT, ventilation imaging for functional avoidance radiotherapy [ 67 ], NCT02528942. To provide practical data for guidance on assessment of patient eligibility, planning strategies and methods of assessment for functional treatment plans, Waxweiler et al recently published a complete virtual trial using retrospective data from 96 LA-NSCLC patients [ 68 ]. Their functional planning demonstrated than an average reduction of 2.8 Gy to the mean lung dose can be expected relative to standard thoracic plans.…”
Section: New Frontiersmentioning
confidence: 99%
“…This retrospective work on 4D CT ventilation imaging has provided the framework for design of clinical trials using 4D CT, ventilation imaging for functional avoidance radiotherapy [ 67 ], NCT02528942. To provide practical data for guidance on assessment of patient eligibility, planning strategies and methods of assessment for functional treatment plans, Waxweiler et al recently published a complete virtual trial using retrospective data from 96 LA-NSCLC patients [ 68 ]. Their functional planning demonstrated than an average reduction of 2.8 Gy to the mean lung dose can be expected relative to standard thoracic plans.…”
Section: New Frontiersmentioning
confidence: 99%
“…This personalization of treatment is especially important in patients with non-small cell lung cancer (NSCLC), who are known to have comorbidities and functional lung defects that change during the course of fractionated RT (1316). Recent clinical studies have shown significant differences between anatomic-and functional-guided radiation treatment plans using a variety of functional imaging modalities, such as single-photon emission computed tomography (SPECT) (1720), 4-dimensional computed tomography (CT) (2124), and hyperpolarized magnetic resonance imaging (25, 26). Although preliminary studies have predicted toxicity reduction using functional-guided RT (27, 28), further work is still required to explicitly understand normal-tissue dose-function response and its effect on radiation-induced lung toxicity (RILT) incidence.…”
Section: Introductionmentioning
confidence: 99%
“…), as well as the potential dosimetric consequences of IJF on radiotherapy functional avoidance planning studies (such as those in Ref. ).…”
Section: Discussionmentioning
confidence: 99%